2018
DOI: 10.1016/j.neuroimage.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

The multidimensional representational space of observed socio-affective touch experiences

Abstract: Observed touch interactions provide useful information on how others communicate with the external world. Previous studies revealed shared neural circuits between the direct experience and the passive observation of simple touch, such as being stroked/slapped. Here, we investigate the complexity of the neural representations underlying the understanding of others' socio-affective touch interactions. Importantly, we use a recently developed touch database that contains a larger range of more complex social and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 92 publications
12
59
0
Order By: Relevance
“…In line with earlier research by others [54] and ourselves [19], we expect that on top of this univariate selectivity there will also be high multi-voxel selectivity for the distinction between social and nonsocial touch videos. The multiple regression analysis confirmed that almost every implicated ROI represents the distinction between social vs. non-social touch scenes, even after controlling for the effects of all the other regressor variables (e.g., low-level visual features and motor response).…”
Section: Neural Representations Underlying Observed Social Versus Nonsupporting
confidence: 85%
See 4 more Smart Citations
“…In line with earlier research by others [54] and ourselves [19], we expect that on top of this univariate selectivity there will also be high multi-voxel selectivity for the distinction between social and nonsocial touch videos. The multiple regression analysis confirmed that almost every implicated ROI represents the distinction between social vs. non-social touch scenes, even after controlling for the effects of all the other regressor variables (e.g., low-level visual features and motor response).…”
Section: Neural Representations Underlying Observed Social Versus Nonsupporting
confidence: 85%
“…In our previous study in NT adults, we demonstrated that individual differences in the strength of neural representations of socio-affective touch in the somatosensory cortex were associated with individual differences in the attitude towards social touch in daily life [19]. Here we further extend these findings and connect the neuroscientific findings with core pervasive autistic traits.…”
Section: Neural Correlates Of Individual Variability In Touch Avoidansupporting
confidence: 76%
See 3 more Smart Citations